(untitled) (Malaysian Management Journal, 2019)
Muslim consumers nowadays are aware of the ingredients in foods thus making them more selective in choosing foods that they want to purchase and consume. Currently, there are no profiles of small and medium entreprises (SME) which have halal certificates, especially in Jambi Province. The main purpose of this research is to find the performance model of SME halal certified food. The hypotheses of this study are: (1) Entrepreneurial orientation significantly influences the consumer engagement of SME halal food (2) Entrepreneurial orientation significantly influences the entrepreneurial marketing of SME halal food (3) Entrepreneurial marketing significantly influences consumer engagement of halal food. (4) Consumer engagement significantly influences the business performance of halal food. The data for the study were collected from primary and secondary sources. Technical data collection was done through the survey sample, field observation, and literature study. The research design uses the mixed method. Research samples comprised 250 halal food SMEs in Jambi Province, Indonesia. The data analysis technique was done using the structural equation (SEM) model and the SmartPLS 3.0 programme. The result shows a positive influence between the entrepreneurial orientation and the consumer engagement on halal food SME’s business performance in Jambi Province. This study will have both managerial implications for practitioners in Indonesia as well as those in other countries and academic implications for researchers who are interested in increasing SME’s business performance.